Peran NGO dalam Pengembangan Masyarakat Agribisnis untuk Mewujudkan Sustainable Development Goals - Fachri, Ahmad; Sultani, Sultani (CULTIVATE: Journal of Agriculture Science, 2025)
This study aims to analyze the role of Non-Governmental Organizations (NGOs) in the development of agribusiness communities and their contribution to achieving the Sustainable Development Goals (SDGs). Agribusiness has a strategic role in improving community welfare, especially in rural areas, but still faces challenges such as limited access to capital, low technological literacy, weak marketing networks, and limited sustainable resource management. This study uses a literature study method with a systematic approach to scientific articles and relevant research reports for the period 2016–2025, which are searched through Google Scholar, Scopus, and DOAJ. The research findings show that NGOs play a role in empowering farmers through training, mentoring, facilitating access to capital, strengthening institutions, marketing assistance, and public policy advocacy. This role not only increases farmer independence and welfare but also strengthens the agribusiness sector's contribution to achieving the SDGs, particularly in poverty alleviation, food security, quality education, decent work and economic growth, reduced inequality, sustainable consumption and production, and strong institutions. Thus, NGO play a role in developing agribusiness communities to realize sustainable development goals.